Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.cell.2011.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Activation of Innate Immune Pattern-Recognition Receptor RIG-I by Viral RNA

Abstract: RIG-I is a key innate immune pattern-recognition receptor that triggers interferon expression upon detection of intracellular 5'triphosphate double-stranded RNA (5'ppp-dsRNA) of viral origin. RIG-I comprises N-terminal caspase activation and recruitment domains (CARDs), a DECH helicase, and a C-terminal domain (CTD). We present crystal structures of the ligand-free, autorepressed, and RNA-bound, activated states of RIG-I. Inactive RIG-I has an open conformation with the CARDs sequestered by a helical domain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
732
5
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 581 publications
(792 citation statements)
references
References 71 publications
30
732
5
7
Order By: Relevance
“…The activity of RIG-I is auto-repressed through intramolecular interaction between the CARD and the RD, and upon viral dsRNA binding, conformational change of RIG-I results in the release of CARDs from RD repression, leading to the association with the adaptor protein MAVS for the initiation of antiviral signaling cascade [11,33,35,36]. It has been shown that the intact tandem CARDs are essential and sufficient for signaling [9,36,37], and mammalian RIG-I mutants with a CARD deletion or CARD point mutations (T55I or S183I) all function as a dominant inhibitor in its signaling [9,11,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of RIG-I is auto-repressed through intramolecular interaction between the CARD and the RD, and upon viral dsRNA binding, conformational change of RIG-I results in the release of CARDs from RD repression, leading to the association with the adaptor protein MAVS for the initiation of antiviral signaling cascade [11,33,35,36]. It has been shown that the intact tandem CARDs are essential and sufficient for signaling [9,36,37], and mammalian RIG-I mutants with a CARD deletion or CARD point mutations (T55I or S183I) all function as a dominant inhibitor in its signaling [9,11,38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the intact tandem CARDs are essential and sufficient for signaling [9,36,37], and mammalian RIG-I mutants with a CARD deletion or CARD point mutations (T55I or S183I) all function as a dominant inhibitor in its signaling [9,11,38]. It has also been revealed in mammals that the RIG-I downstream signaling via MAVS requires the recruitment of TRIM25 and other ubiquitination enzymes to synthesize unanchored K63-linked polyubiquitin chains binding to the CARD domains [36,37,39,40]. In the present study, RIG-Ia, the insertion variant of RIG-I with additional 38-aa residues in the CARD2 domain had no direct role in the activation of type I IFN promoter or antiviral defense, although the expression level of RIG-Ia could be induced under E. tarda or SVCV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Les structures tridimensionnelles de la protéine RIG-I entière de canard [4] et de formes tronquées comportant les domaines CARD-hélicase, hélicase, et hélicase-CTD, complexées ou non avec de l'ARNdb, viennent d'être simultanément résolues à l'automne 2011 par quatre équipes, dont la nôtre, travaillant sur le RIG-I de canard, humain ou de la souris [4][5][6][7]. Les informations obtenues sont complémentaires.…”
Section: Structure Du Domaine Hélicase De Rig-i Et Interaction Avec Lunclassified
“…Les informations obtenues sont complémentaires. Elles convergent vers un modèle cohérent des changements de conformation responsables de la commutation d'un état autoréprimé inactif (ou dormant) vers un état activé [4][5][6][7]. La première hélice  remonte vers Hel1 qui est prise en sandwich par la seconde hélice .…”
Section: Structure Du Domaine Hélicase De Rig-i Et Interaction Avec Lunclassified
See 1 more Smart Citation